ROLE OF INTEGRATION PROCESSES IN HARMONIZATION OF THE LEGAL SYSTEMS OF CENTRAL ASIANCOUNTRIES - Z.K.Ayupova; D.U. Kussainov (Academic Journal of Physical and Chemical Sciences, 2019)
Legal integration is the modern stage of evolutional development of law, consists of complex of the legal processes, based on the achievement of equilibrium of the legal systems of the states, within the framework of single model of the legal system. Doctrine shows the different forms of the evolutional development of law, the legal integration between the legal systems of the states.Undoubtedly, the problem of scientific understanding of the relation of integration association and international law is one of the most urgent and complex issues of theory and practice in modern jurisprudence. Interaction, mutual influence, differentiation of terms of reference for the international and integration law under the influence of modern globalization processes, multidisciplinary scientific problem, which has important theoretical and practical value. Exploring ways of mutual penetration of the rules of one legal system to another, as well as to what extent the norms of integration law may come into conflict with obligations of states under international law and how integration associations should act in these cases is the key issue.